PERKEMBANGAN DAN PENERAPAN KURIKULUM SERTA PEMBELAJARAN DI MASA PANDEMI COVID-19 - Iskandar, Sofyan; Rosmana, Primanita Sholihah; Anggraeni, Isni Putri; Sulistyorini, Septi; Anisa, Puja Sahwa (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
In preventing the spread of the COVID-19 virus, the Government issued regulations for distance learning. Distance learning makes education units, educators, and students experience various obstacles. To overcome the problems and obstacles in implementing bold learning, the curriculum is an important option so that learning can run effectively and efficiently. Thus, the Government issued a Decree from the Ministry of Education and Culture related to the option to restore learning during the Covid-19 pandemic, namely in the form of a curriculum. The learning recovery curriculum includes the 2013 Curriculum, the Emergency Curriculum (Simplification of the 2013 Curriculum), and the Prototype Curriculum. The purpose of this study is to discuss the development and implementation of the curriculum in building optimal learning during the COVID-19 pandemic. The method used in this research is to find a qualitative method with a literature study. The data collected in this study were sourced from various articles in national journals, online news, and also in literature books related to curriculum and learning during the COVID-19 pandemic.